2022
DOI: 10.3390/ijerph19148531
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Feasibility of a Future Integrated Larger-Scale Epidemiological Study to Evaluate Health Risks of Air Pollution Episodes in Children

Abstract: Air pollution exposure can lead to exacerbation of respiratory disorders in children. Using sensitive biomarkers helps to assess the impact of air pollution on children’s respiratory health and combining protein, genetic and epigenetic biomarkers gives insights on their interrelatedness. Most studies do not contain such an integrated approach and investigate these biomarkers individually in blood, although its collection in children is challenging. Our study aimed at assessing the feasibility of conducting fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…To our knowledge this is the first study conducted in children, in the context of short-term exposure to PM, where FeNO and U-CC16 were measured, where their mutual association was investigated, and where specific consideration was taken for the genetic background and renal handling adjustment when using U-CC16 as a biomarker. Although our study involved only a limited number of participants, as it was initially conceived as a feasibility study (Nauwelaerts et al, 2022a), relevant and statistically significant associations were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge this is the first study conducted in children, in the context of short-term exposure to PM, where FeNO and U-CC16 were measured, where their mutual association was investigated, and where specific consideration was taken for the genetic background and renal handling adjustment when using U-CC16 as a biomarker. Although our study involved only a limited number of participants, as it was initially conceived as a feasibility study (Nauwelaerts et al, 2022a), relevant and statistically significant associations were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…On the first time point of the study, a saliva sample was collected to investigate the CC16 SNP G38A genotype. More details on the complete set-up of the field study, on the measurements and sampling have been described elsewhere, where we have reported on the set-up and logistic bottlenecks for this type of studies (Nauwelaerts et al, 2022a).…”
Section: General Health Parameters and Noninvasive Samplingmentioning
confidence: 99%
See 3 more Smart Citations